Finite element method usage in determining pressure distribution of periodontal tissues on maxillary canine as result of orthodontic force - E. Elih; Tono S. Hambali; Jono Salim; Endah Mardiati (Padjadjaran Journal of Dentistry, 2011)
The purpose of this study is to obtain data of pressure distribution on canine periodontal tissues due to the orthodontic force generated by various types of motion using the Finite Element Method. The development of digital technology creates a numerical analysis for orthodontic treatment that can be done by performing 3-D reconstruction by scanning the maxillary canine teeth with a CT scan so that 255 cross-sectional images is obtained. 3 D model is then processed using the Finite Element Method to obtain the pressure distribution on the periodontal tissues caused by tipping movements, bodily, torque, roots, rotation, and extrusion. The analysis used was the analysis of qualitative and quantitative analysis. The results showed that the maximum pressure that occurs in the periodontal tissues caused by a variety of movements ranging from 3.3 x 10-3MPa to 2.9 x 10-2 MPa. This indicates that the force exerted on each movement produces maximum pressure that exceeds capillary pressure was 2 x 10-3 MPa.